2018
DOI: 10.1021/acs.oprd.8b00090
|View full text |Cite
|
Sign up to set email alerts
|

Development of an SNAr Reaction: A Practical and Scalable Strategy To Sequester and Remove HF

Abstract: A simple and operationally practical method to sequester and remove fluoride generated through the S N Ar reaction between amines and aryl fluorides is reported. Calcium propionate acts as an inexpensive and environmentally benign in situ scrubber of the hydrofluoric acid byproduct, which is simply precipitated and filtered from the reaction mixture during standard aqueous workup. The method has been tested from 10 to 100 g scale of operation, showing >99.5% decrease in fluoride content in each case. Full mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
(40 reference statements)
1
9
0
Order By: Relevance
“…1 H NMR (600 MHz, CDCl 3 ) δ 7.86 (dt, J = 8.8, 2.2 Hz, 2H, 2-CH), 7.30 (t, J = 8.0 Hz, 4H, 3′-CH), 7.14 (d, J = 8.0 Hz, 4H, 2′-CH), 7.11 (t, J = 8.0 Hz, 2H, 4′-CH), 6.99 (dt, J = 8.8, 2.2 Hz, 2H, 3-CH), 4.35 (q, J = 7.2 Hz, OCH 2 ), 1.36 (t, J = 7.2 Hz, CH 2 CH 3 ) ppm; 13 C­{ 1 H} NMR (150 MHz, CDCl 3 ) δ 166.5 (CO 2 ), 152.0 (4-CN), 146.9 (1′-CN), 130.9 (2-CH), 129.7 (3′-CH), 125.9 (2′-CH), 124.5 (4′-CH), 122.7 (1-C), 120.3 (3-CH), 60.7 (OCH 2 ), 14.6 (CH 2 CH 3 ) ppm; 15 N NMR ( 1 H– 15 N HMBC projection, 60 MHz, CDCl 3 ) δ 99.9 ppm. The spectral data are consistent with those reported in the literature …”
Section: Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…1 H NMR (600 MHz, CDCl 3 ) δ 7.86 (dt, J = 8.8, 2.2 Hz, 2H, 2-CH), 7.30 (t, J = 8.0 Hz, 4H, 3′-CH), 7.14 (d, J = 8.0 Hz, 4H, 2′-CH), 7.11 (t, J = 8.0 Hz, 2H, 4′-CH), 6.99 (dt, J = 8.8, 2.2 Hz, 2H, 3-CH), 4.35 (q, J = 7.2 Hz, OCH 2 ), 1.36 (t, J = 7.2 Hz, CH 2 CH 3 ) ppm; 13 C­{ 1 H} NMR (150 MHz, CDCl 3 ) δ 166.5 (CO 2 ), 152.0 (4-CN), 146.9 (1′-CN), 130.9 (2-CH), 129.7 (3′-CH), 125.9 (2′-CH), 124.5 (4′-CH), 122.7 (1-C), 120.3 (3-CH), 60.7 (OCH 2 ), 14.6 (CH 2 CH 3 ) ppm; 15 N NMR ( 1 H– 15 N HMBC projection, 60 MHz, CDCl 3 ) δ 99.9 ppm. The spectral data are consistent with those reported in the literature …”
Section: Methodssupporting
confidence: 91%
“…The spectral data are consistent with those reported in the literature. 75 tert-Butyl 4-(diphenylamino)benzoate was isolated as byproduct with 4 in procedures when NaBHT was generated from BHT and NaOtBu, as described in procedures above.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…On 100 g scale in a steel vessel at 100 °C and using aqueous ammonia (13 equiv) in NMP as solvent, fluoropyridine 7 underwent ammonolysis to give, after extraction and concentration, aminopyridine 8 in 93% assayed yield by 1 H NMR as a highly discolored solid. Although we initially were concerned about the generation of HF and its corrosive/etching properties, we did not visually observe any damage to the reaction vessel, probably due to the large excess of ammonia used . To avoid the need for chromatography for purification of 8 , a quick screen of suitable solvents for crystallization was performed.…”
Section: Resultsmentioning
confidence: 99%
“…the Pbf-protected product 10a) and safety issues, we decided to investigate the influence of various fluoride scavengers as additives in our three-component process. [24][25] An extensive study (not shown), revealed, that most common scavengers either led to a decreased yield, a decreased stereoselectivity or a combination of both. Yet a combination of CaCO3, tartaric acid and molecular sieves 4Å, each already employed a HF scavenger by itself, did afford the desired arylglycine in high yields and enantioselectivities (entry 11).…”
Section: Scheme 3 Initial Experimentsmentioning
confidence: 99%